A Unique Case of Melorheostosis Presenting with Two Radiologically Distinct Lesions in the Shoulder. (6th November 2017) - Elsheikh, Ahmed A.; Pinto, Rohan S.; Mistry, Alpesh; Frostick, Simon P.
Abstract : Melorheostosis is a rare, nonhereditary, benign, mesenchymal condition of unknown aetiology affecting the bones and surrounding tissues. A male patient complaining of left shoulder pain, swelling, and mildly limited range of motion has an exclusive combination of the classic dripping wax lesion in the scapula and the myositis ossificans-like lesion in the deltoid muscle; this combination is the first to be reported in the shoulder. Both lesions showed typical findings of melorheostosis in radiographs, CT, MRI, and bone scan. This case has a stationary course over the follow-up period, and no specific treatment is needed in due course.